Earned income tax credit experiments in the People's Republic of China - Li Gan; Xiongfei Guo; Qing He; Junhui Wang (Asian Development Bank Institute (ADBI), 2020)
As more households in the People's Republic of China (PRC) are lifted out of poverty, it becomes increasingly difficult to address the remaining poor by implementing traditional cash transfer programs due to inaccurate identification and the welfare dependency issue. One solution is to implement an incentive-compatible transfer program such as the Earned Income Tax Credit (EITC) in the United States. Starting in 2014, the China Household Finance Survey (CHFS) conducted a series of experiments. Evaluations present unambiguously strong evidence that EITC increases labor supply, earning, and expenditure in the PRC. Inspired by the early success, many Chinese local governments have been trying to come up with their own EITC-like programs or trials. This paper will discuss some of the ongoing experiments or trials in the PRC.
Keywords: H24; 330; People's Republic of China; anti-poverty; EITC; field experiment